2016
DOI: 10.18632/oncotarget.11414
|View full text |Cite
|
Sign up to set email alerts
|

p53, a potential predictor ofHelicobacter pyloriinfection-associated gastric carcinogenesis?

Abstract: Helicobacter pylori (H. pylori) is an ancient and persistent inhabitant of the human stomach that is closely linked to the development of gastric cancer (GC). . Emerging evidence suggests that H. pylori strain interactions with gastric epithelial cells subvert the best- characterized p53 tumour suppressor pathway. A high prevalence of p53 mutations is related to H. pylori infection. H. pylori also accelerates p53 protein degradation by disturbing the MDM2-P53 feedback loop. Additionally, H. pylori triggers the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 103 publications
2
18
2
1
Order By: Relevance
“…and signaling pathways (PI3 kinase‐AKT, β‐catenin‐WNT, and NF‐κB pathways, etc.) were confirmed to play an important role in H. pylori pathogenesis . However, a database‐based comprehensive analysis of genes and signaling pathways involved in H. pylori pathogenesis is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…and signaling pathways (PI3 kinase‐AKT, β‐catenin‐WNT, and NF‐κB pathways, etc.) were confirmed to play an important role in H. pylori pathogenesis . However, a database‐based comprehensive analysis of genes and signaling pathways involved in H. pylori pathogenesis is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation of p53-mediated cellular processes, such as apoptosis and cell cycle control signaling pathways, have been associated with the progression of gastric cancer [ 12 , 26 , 29 , 30 ]. In the current study, the TCGA database was interrogated to identify deregulated p53-associated cell cycle and apoptosis genes in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation and accumulation of p53 is a hallmark of carcinogenesis, including GC, in which higher p53 levels in malignant tissue are associated with poor prognosis (Yildirim et al, 2015;Zhou et al, 2016). H. pylori induction of p53 expression has been described in chronic gastritis and preneoplasic lesions (such as intestinal, metaplasia and dysplasia in adults), especially those associated with CagA-positive strains (Teh et al, 2002;Li et al, 2016). Pediatric studies assessed in this review showed contradictory results, with p53 overexpressed in gastric tissue of H. pylori infected children, and directly correlated with gastritis, the magnitude of inflammatory cell infiltration and H. pylori tissue density in two studies (Ozturk et al, 2005;Saf et al, 2015); while on the other hand two other studies showed similar expression levels in infected and non-infected children (Nardone et al, 2001;Villarreal-Calderon et al, 2014).…”
Section: Transcription Factorsmentioning
confidence: 99%